Recommended protection scheme setting coordination for nine busbars transmission grid - Saleem, Radhwan Mohammed (2015)
Protection system is one of the important parts of the power system. The protection system can be accepted if and only if it is efficient, reliable and realizes some requirements. For protection of transmission line three stepped distance protection can provide remote backup protection to transmission line by zone 2 and zone 3, but during the calculation of operation setting for different protection zones of the distance relays, some problems have been raised (overlap and under reach). These problems cause improper trips in the network. The aims at overcoming the problems are by taking into consideration the specifications of the adjacent transmission lines, the effect of arc resistance, earth resistance and the effect of remote infeed. The line protection schemes are composed of distance relays and directional overcurrent relays where the setting of the relays must be computed considering both relays. Separate relay computation would lead to loss of selectivity. The standard IEC 60255 combined with the considerations of zone 2 tripping time have been used in order to overcome the coordination problems with the main protection (distance protection) as a local protection and to provide remote backup protection to the other overcurrent relays in the grid. In this project, the protection of the transmission lines in typical IEEE, 9- busbars grid has been investigated in detail. The proper settings for both main protection (i.e. distance protection) and backup protection (i.e. overcurrent protection) devices have been determined. MATLAB and ETAP have been used as simulating tools to validate the protection settings techniques of the relays. Three approaches of settings have been used for the mentioned relays. The results show the proper settings of the both relays of the entire project.